Correção de heterogeneidades para feixes de fótons de 6 MeV: comparações entre algoritmos de cálculo e medidas com TLD - Baptista, Cláudia Gonçalves (2009)
This work presents the dose variations obtained when phantoms of different electronic densities were used, simulating fat tissue, muscle, bones and air cavities, comparing experimental data with a 6 MeV photon beams and the values calculated by the treatment planning system algorithms. Thermoluminescent dosimeters were positioned above, inside and below each phantom measuring the dose along the depth and along a profile. The computational simulation was done by two algorithms that are part of Eclipse version 8.5: Pencil Beam Convolution and Analytical Anisotropic Algorithm. Comparing doses at the same point, with and without heterogeneities, percentages of 12% were found when heterogeneity correction was not used. These results also show which of the algorithms approaches better to the experimental values, becoming more reliable.